A Brief Discussion on the Influence and Significance of the Task Dismantling Teaching Method on the Political Education Environment in Colleges and Universities. (31st July 2022) - Chen, Yue
Abstract : The ideological and political education in colleges and universities shoulders the important task of defending the Marxist ideology. It has strong value selectivity and a high degree of political principle. For a long time, the indoctrination teaching method has often been regarded as the only way to arm newcomers with Marxist beliefs from the outside to the inside. However, through the reform and opening up and the development of informatization in Chinese society, the traditional indoctrination teaching mode has become more and more inefficient and inactive show. In fact, the education of ideals and beliefs can only emit dazzling sparks when it collides with the experience world of learners. At present, the ideological and political education in colleges and universities should be fully connected with the reality of personal and social development. As far as ideological and political theory education is concerned, the central government has also issued relevant documents, mainly to strengthen the ideological and political education of college students. For this reason, it is necessary to further explore the deficiencies in the ideological and political theory education in colleges and universities, and make comprehensive improvements. By discussing the reform of ideological education in colleges and universities and studying the specific connotation of task disassembly teaching, the paper analyzes and discusses the corresponding suggestions and strategies of the political education reform of colleges and universities.